Pharmacodynamic Kill Kinetics and Minimum Bactericidal Concentration of Citrus aurantifolia Lime Peel Ethanolic Extract: A Comparative Colony-Count Study against Two Skin-Associated Gram-Positive Pathogens - Indrayati, Lyna Lestari; Huda, Choirul (CV. Nusantara Scientific Medical, 2023)
While inhibition zone measurements characterise bacteriostatic activity, colony enumeration after extract exposure is required to quantify true bactericidal kill kinetics. This study determined the minimum bactericidal concentration (MBC), percentage colony reduction, log10 reduction, and surviving colony-forming unit (CFU) profiles of Citrus aurantifolia lime peel ethanolic extract against Propionibacterium acnes ATCC 6919 and Staphylococcus epidermidis ATCC 12228 across 14 concentrations (0.5–150 mg/mL) using the streaking-colony counting method on Plate Count Agar (PCA). Pharmacodynamic modelling employed the Hill (Emax) equation to characterise the concentration–effect relationship. Concentration-dependent colony reduction was observed for both organisms from 0.5 mg/mL. The MBC was 40 mg/mL against P. acnes (98.24% reduction; log10 reduction 1.99; 42 surviving CFU from N₀ 2391) and 50 mg/mL against S. epidermidis (98.80% reduction; log10 reduction 1.99; 30 surviving CFU from N₀ 2495). The MBC:MIC ratio of 40–50 indicates predominantly bacteriostatic activity at low concentrations transitioning to bactericidal activity at ≥40 mg/mL. Hill equation fitting yielded EC50 of 9.8 mg/mL (P. acnes) and 12.1 mg/mL (S. epidermidis). These pharmacodynamic parameters provide rational concentration targets for antiseptic topical formulation development.